2015
DOI: 10.1177/0098628315620889
|View full text |Cite
|
Sign up to set email alerts
|

Study Abroad in Psychology

Abstract: Despite the prominence of study abroad programs, few are offered in the field of psychology. The current study sought to investigate the impact of study abroad programs in psychology through a comparison of study abroad and domestic student cultural competencies. Participants included 104 undergraduate students enrolled in either a psychology study abroad program or domestic psychology courses who completed pre–post Cross-Cultural Adaptability Inventory measures. Results indicated greater emotional resilience,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Experiential learning can be utilized beyond geographical borders through study abroad field trips. These excursions bring a level of dynamism where the curriculum is infused with the excitement of traveling to another country (Earnest et al, 2016;Greenfield et al, 2012). Students can interact with an unfamiliar cultural environment and apply their knowledge to the course work (Greenfield et al, 2012).…”
Section: Experiential Learning Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Experiential learning can be utilized beyond geographical borders through study abroad field trips. These excursions bring a level of dynamism where the curriculum is infused with the excitement of traveling to another country (Earnest et al, 2016;Greenfield et al, 2012). Students can interact with an unfamiliar cultural environment and apply their knowledge to the course work (Greenfield et al, 2012).…”
Section: Experiential Learning Theorymentioning
confidence: 99%
“…They found that study abroad provides the opportunity to incorporate new knowledge into existing values and beliefs -an experience that fosters global citizenship. Numerous other studies report that study abroad trips serve as a unique platform for reflection, social development and personal growth (Earnest et al, 2016;McPhee & Przedpelska, 2018;Philip et al, 2017).…”
Section: Experiential Learning Theorymentioning
confidence: 99%
“…The language skills alone can contribute to a boost in earnings for workers (Saiz & Zoido, 2002). Recent research shows the benefits of study abroad experiences as impactful across several key psychological attributes (Earnest, Rosenbusch, Wallace-Williams & Keim, 2016). Study abroad experiences appear to boost students' emotional resilience, flexibility and openness, perceptual acuity, and personal autonomy (Earnest, Rosenbusch, Wallace-Williams & Keim, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Intercultural competence is essential for professionals whose career requires frequent interactions with increasingly diverse populations such as clinical psychologists, counselors, and professors (Earnest et al, 2016;Swazo & Celinska, 2014). Furthermore, knowledge of the relevance of culture to the study of human behavior and cognition can have significant impacts on those who conduct research in psychology (Shupe, 2013).…”
mentioning
confidence: 99%
“…One of the best ways to facilitate such cooperation and communication skills is to place students in direct contact with other cultures, as studies have shown that study abroad programs can enhance the development of intercultural competence (e.g., Anderson et al, 2006;Earnest et al, 2016;Pederson, 2009). Study abroad programs for psychology students have been found to improve not only intercultural competence but also emotional resilience, flexibility and openness, and perceptual acuity, characteristics that are also imperative for practitioners of psychology (Earnest et al, 2016). Furthermore, studies have found that psychology majors enrolled in programs that include study abroad opportunities perform better on standardized tests, have higher program completion rates, and have higher rates of graduate school attendance (Stoloff et al, 2015).…”
mentioning
confidence: 99%